Answer:
Step-by-step explanation:
hello :
(x-4)²(x+3)² = -1
means : ((x-4)(x+3))² = - 1 this equation has no solutions in R
because for all x in R : ((x-4)(x+3))² ≥ 0
<span>relating to or denote a system of numbers and arithmetic based on the number ten, tenth parts, & powers of ten.</span>
● 3x^2 - 10 = 0
Add 10 to both sides
● 3x^2 - 10 + 10 = 10
● 3x^2 = 10
Divide both sides by 3
● 3x^2/3 = 10/3
● x^2 = 10/3
● x = √( 10/3 ) or x = - √( 10/3 )
● √(10/3) + (-√(10/3)) = 0
● √(10/3) × -√(10/3) = -10/3